Virtual cluster control for active distribution system using Pinning-based distributed secondary control. (July 2019) - Liu, Wei; Gu, Wei; Sheng, Wanxing; Song, Xiaohui; Gao, Fei
Highlights: A novel VCC is proposed to facilitate a powerful control structure for an ADS. A virtual cluster pinning method is proposed to control part of the agents. The pinning-based distributed secondary control (PBDSC) scheme is proposed. Abstract: To facilitate a powerful control for an active distribution system (ADS) with high permeability distributed generators (DGs), a novel virtual cluster control (VCC) that includes a virtual cluster pinning and the pinning-based distributed secondary control (PBDSC) is proposed. The basic objectives of the proposed control are respectively: (1) to control an ADS by pinning the virtually partitioned clusters, which entitled virtual microgrid clusters (VMGCs) and virtual power plant clusters (VPPCs), (2) to implement PBDSC in VMGC and VPPC based on adaptive pinning, and (3) to adapt the uncertain communication topology changes in each cluster. Additionally, the proposed control drastically reduces the control dimension of an ADS and achieves global coordination and local autonomy by making fully use of the features and advantages of both VMGCs and VPPCs. The proposed control is embedded in the IEEE 123-bus system on PSCAD/EMTDC and MATLAB platform, its validity and applicability is investigated by multiple simulation cases.